Effect of micro-arc oxidation coatings with graphene oxide and graphite on osseointegration of titanium implants-an in vivo study - Tekin, Bahar; Dundar, Serkan; Tekin, Samet; Sukuroglu, Ebru Emine; Khurshid, Zohaib; Ezgi, Yusuf; Faheemuddin, Muhammad (Elsevier, 2024)
Background: This in vivo study evaluated the effect of graphene oxide and graphite coatings, coupled with the micro-arc oxidation (MAO) surface roughening technique, known for their mechanical strength, chemical stability, and antibacterial properties. The main objective was to assess the degree of improvement in osseointegration of titanium implants resulting from these interventions. Materials and methods: In this study, 32 female rats were utilized and randomly allocated into four groups (n = 8 each): machined surface titanium implants (control), those roughened by the MAO method, those coated with graphene oxide-doped MAO, and those with a graphite-doped MAO coating. Titanium implants were surgically placed in the right tibia of the rats. Rats undergoing no additional procedures during the 4-week experimental period were sacrificed at the end. Then, the implants and surrounding bone tissues were separated and embedded in acrylic blocks for reverse torque analysis. Using a digital torque device, the rotational force was applied to all samples using a hex driver and racquet until implant separation from the bone occurred, with the corresponding values recorded on the digital display. Then, statistical analysis was performed to analyze the data. Results: No statistically significant difference between the groups was observed in the biomechanical bone-implant connection levels (N/cm) (P = 0.268). Post-hoc tests were not required because no discernible differences were identified between the groups. Conclusion: Within the scope of this study, implants treated with the MAO method, along with those coated with graphene oxide- and graphite-doped MAO method, did not exhibit significant superiority in terms of osseointegration compared to machined surface titanium implants.
Keywords: Coating; Dental implants; Graphite; Graphene oxide; Micro -arc oxidation; Osseointegration